2014
DOI: 10.4317/jced.51284
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impacted and supernumerary teeth in the North Indian population

Abstract: Objectives: Dental impaction is a very frequent problem. Supernumerary teeth, or hyperdontia, are the presence of additional teeth to the normal series in the either of the dentition. The presence of impacted and/or supernumerary teeth can cause various complications. The objective of the present study was to determine the prevalence of impacted and supernumerary teeth in the North Indian population. Study Design: The panoramic radiographic records of 4750 patients attending the Department of Oral Medicine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 15 publications
9
56
4
2
Order By: Relevance
“…However it is lower than that reported by Aydin et al (2004) who found a 3.29% in a population of Turkey and found by Patil & Maheshwari (2014) which was 9.7% in India.…”
Section: Discussioncontrasting
confidence: 52%
“…However it is lower than that reported by Aydin et al (2004) who found a 3.29% in a population of Turkey and found by Patil & Maheshwari (2014) which was 9.7% in India.…”
Section: Discussioncontrasting
confidence: 52%
“…Such differences in prevalence rates may be due to differences in the genetic and ethnic backgrounds of the patients involved. A recent study in an Indian population indicated that the prevalence of tooth impaction was 16.8%, within the range 5.6–18.8%, as reported in earlier studies 10 11…”
Section: Discussionsupporting
confidence: 81%
“…Mesiodens is more common in the permanent than in the primary dentition. The incidence of occurrence of mesiodens in Indian population was estimated to range from 0 to 1.4% [5]. Review done by Meighani & Pakdaman in 2010 found that the prevalence of mesiodens in various studies from 1932 to 2008 is between 0.09% and 2.05% [6].…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that 80% to 90% of all supernumerary teeth are found in the maxilla and half are found in the anterior region [9]. A sex-linked pattern has also been proposed, as males are affected twice as frequently as females [5,6,9]. Mesiodens can occur individually or as multiples (mesiodens), may appear unilaterally or bilaterally, and often do not erupt [6,9].…”
Section: Discussionmentioning
confidence: 99%